(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2022)
Several Mg-Coumarinolates and Al-Coumarinolates doped with different concentrations of Quinoline were synthesized by simple chemical synthesis method and their PL spectra were studied. Usually, pure coumarin along with the chelates show weak luminescence and the emission is witnessed around 450 nm with excitation around 350 nm. Hence, such chelates do not find any practical applications. Addition of quinoline in lesser amount affects the emission and excitation of Mg-Coumarin and Al-Coumarin considerably. Intense photoluminescence is observed in these Mg based mixed chelates. In all samples, a well-defined emission band at 490 nm is observed with broad excitation in 350 nm to 470 nm range. Hence good overlap of excitation with 420 nm and 440 nm LED emission makes these materials suitable for white LED applications.